2006
DOI: 10.1051/jp4:2006134191
|View full text |Cite
|
Sign up to set email alerts
|

Response of pre-loaded laminate composite plates subject to high velocity impact

Abstract: Abstract. An experimental and analytical study of two cases of static preload (uniaxial and biaxial) was made to detennine the response of structural plate elements subjected to high velocity impacts under inplane tensile preloading conditions. The results were compared with those obtained in non-preloading specimens. Rectangular specimens were used for the uniaxial and non-preload tests, while cross-shaped specimens were used for the biaxial tests. The impacts were made by spherical projectiles travelling at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
3
18
0
2
Order By: Relevance
“…In all of the structures the maximum damage areas were reached in the areas surrounding the ballistic limit [7]. For velocities below the ballistic limit the damage area increased with velocity, while for velocities greater than the ballistic limit this decreases with the increase in velocity.…”
Section: Resultsmentioning
confidence: 69%
“…In all of the structures the maximum damage areas were reached in the areas surrounding the ballistic limit [7]. For velocities below the ballistic limit the damage area increased with velocity, while for velocities greater than the ballistic limit this decreases with the increase in velocity.…”
Section: Resultsmentioning
confidence: 69%
“…In laminate composites plates, it has been observed that the presence of an in-plane preload altered the damage generated by the impact, and also slightly increased the ballistic limit (García-Castillo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the behaviour of preloaded structures subjected to high-velocity impacts to date have considered only ceramic materials (Bao et al, 2002;Holmquist and Johnson, 2005) or composite materials (García-Castillo et al, 2006). In laminate composites plates, it has been observed that the presence of an in-plane preload altered the damage generated by the impact, and also slightly increased the ballistic limit (García-Castillo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Важность этих исследований подчеркнута в работе [13]. Влияние высокоскоростного удара на баллистические свойства предварительно нагруженных слоистых композитных конструкций исследовалось толь-ко в нескольких статьях [13,21]. Garcia-Castillo в работе [21] изучали влияние высокоскоростного удара на предварительно нагруженные композитные стеклопластиковые пластины.…”
unclassified